The Influence of Wood Moisture Content on the Processes of Freezing and Heating - Ivan Klement; Peter Vilkovský; Tatiana Vilkovská (Applied Sciences, 2021)
In wood processing, wood is exposed to an environmental temperature of less than 0 °C for some time, which mainly occurs during the air drying of wood in the winter months, or when lumber is stored in wood piles outdoors before the kiln drying process. In these cases, the wood freezing process increases the degree of freezing of the wood, subsequently significantly affecting the process of its heating during further processing (for example, in the cutting process). The most common method is heating by humid air, during the hot air drying of wood. We analyzed the temperature profiles on a cross-section of wood and moisture losses due to the freezing process and the size of moisture gradients. We compared theoretical calculations of the time required for defrosting and heating of wood with the experimentally measured values. The results show that the moisture content (MC) of wood has a remarkable effect on the wood freezing process. In samples with an average MC of 35.47%, the temperature drop was faster. After 10 h, the temperatures on the entire cross-section of the samples reached the lowest value of −13.2 °C. In samples with an average initial MC of 81.38%, three stages of temperature reduction in the wood were observed. The temperature dropped and the lowest temperature of −20.11 °C was reached after 24 h. The defrosting and heating process of samples with lower MC was significantly easier. The desired temperature of 65 °C in the middle of the samples was reached in 2 h and 20 min. The total time to defrost and heat the second group of samples (MC > FSP) was 3 h 30 min.